Evaluation of plant-derived commercial products for blast and sheath blight control in rice - D. KRISHNAVENI and G.S. LAHA, K. MURALlDHARAN, C.S. REDDY, (Indian Phytopathology, 2003)
Commercial plant-derived products with or without the active principle azadirachtin, were tested for 5-yearsat 12 sites endemic to rice blast or at 9 sites endemic to sheath blight disease. Most plant-derived products tested reduced disease severity, and also increased grain yield harvests. The degree of disease reductionand yield increase was more pronounced when these products were applied to control blast. The plant-derivedproducts may serve as an effective component in integrated management of rice blast and sheath blight diseases.